2020
DOI: 10.1007/s12264-020-00577-5
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Hypersensitivity as an Indicator of Visceral Inflammation via C-Nociceptor Axon Bifurcation

Abstract: Pain on the body surface can accompany disorders in the deep tissue or internal organs. However, the anatomical and physiological mechanisms are obscure. Here, we provided direct evidence of axon bifurcation in primary C-nociceptive neurons that innervate both the skin and a visceral organ. Double-labeled dorsal root ganglion (DRG) neurons and Evans blue extravasation were observed in 3 types of chemically-induced visceral inflammation (colitis, urocystitis, and acute gastritis) rat models. In the colitis mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
0
8
0
6
Order By: Relevance
“…One hallmark for inflammatory visceral pain manifestation is the development of referred cutaneous mechanical hypersensitivity (Bai et al, 2019; Bielefeldt et al, 2006; Bourdu et al, 2005; Cao et al, 2021; Gao et al, 2021; Jain et al, 2022; Laird et al, 2000; Laird et al, 2002; Lv et al, 2019; Traub et al, 2008; Zhou et al, 2008). Such referred hypersensitivity was also abolished in VGLUT3 Lbx1 -Abl mice, suggesting that VGLUT3 neurons must be part of previously proposed spinal circuits receiving convergent inputs from cutaneous and visceral afferents (Cervero, 2009; Cui et al, 2022; Fang et al, 2021; Fuentes and Christianson, 2018; Gebhart and Bielefeldt, 2016; Luz et al, 2015; Qiao and Tiwari, 2020). Thus, spinal VGLUT3 neurons represent an attractive cellular target for treating allodynia originated from both cutaneous and rectal tissues.…”
Section: Discussionmentioning
confidence: 72%
“…One hallmark for inflammatory visceral pain manifestation is the development of referred cutaneous mechanical hypersensitivity (Bai et al, 2019; Bielefeldt et al, 2006; Bourdu et al, 2005; Cao et al, 2021; Gao et al, 2021; Jain et al, 2022; Laird et al, 2000; Laird et al, 2002; Lv et al, 2019; Traub et al, 2008; Zhou et al, 2008). Such referred hypersensitivity was also abolished in VGLUT3 Lbx1 -Abl mice, suggesting that VGLUT3 neurons must be part of previously proposed spinal circuits receiving convergent inputs from cutaneous and visceral afferents (Cervero, 2009; Cui et al, 2022; Fang et al, 2021; Fuentes and Christianson, 2018; Gebhart and Bielefeldt, 2016; Luz et al, 2015; Qiao and Tiwari, 2020). Thus, spinal VGLUT3 neurons represent an attractive cellular target for treating allodynia originated from both cutaneous and rectal tissues.…”
Section: Discussionmentioning
confidence: 72%
“…Recently, some DRG neurons have been reported to innervate both the skin and the distal colon simultaneously ( Fang et al, 2020 ). In vivo extracellular electrophysiological recordings of those DRG neurons revealed that they robustly respond to both expansions of the distal colon and the mechanical, nociceptive, warm, or cold stimulation of the cutaneous receptive field ( Fang et al, 2020 ). These results indicate that DRG neurons shared by both the skin and the distal colon participate in the transmission or modulation of multiple sensation signals.…”
Section: Discussionmentioning
confidence: 99%
“…Fang in 2021 showed that inflammatory bowel diseases can cause hypersensitivity in a corresponding dermatome. 31 According to his study, this phenomenon reflects the fact that there is common innervation of the skin and visceral organs coming from the bifurcation of the C-nociceptive neurons ( Figure 5 ).
Figure 5 Interrelation between visceral and cutaneous nociceptive neurons.
…”
Section: Tissue Specific Variations Of Nociceptorsmentioning
confidence: 96%